2021
DOI: 10.1002/aelm.202100194
|View full text |Cite
|
Sign up to set email alerts
|

UV‐Sinterable Silver Oxalate‐Based Molecular Inks and Their Application for In‐Mold Electronics

Abstract: A new broadband UV light‐based processing method for a screen printable silver oxalate molecular ink is developed that enables structural electronics to be produced on complex thermoformed 3D objects. The production of these 3D devices is driven by the light‐induced reduction of silver oxalate to form an interfacial silver nanoparticle layer that allows the ink to transition to a viscous liquid intermediate and elongate up to 50% without cracking during thermoforming. Ultimately, this enables the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…[31][32][33] UV treatments are valuable as they can produce conductive traces in 20% of the time required for thermal sintering, however, suitable UV-assisted sintering techniques typically require long processing times relative to IPL and laser sintering, reaching exposure times of up to 40 min. [30,35] Minimizing this time frame while still retaining optimal performance metrics is necessary for UV sintering to be considered a feasible technique for large-scale electrode fabrication. Therefore, microgrid design, trace morphology, surface chemistry, and UV light exposure will therefore all play a critical role in conductive performance and subsequently transparent heater thermal performance efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] UV treatments are valuable as they can produce conductive traces in 20% of the time required for thermal sintering, however, suitable UV-assisted sintering techniques typically require long processing times relative to IPL and laser sintering, reaching exposure times of up to 40 min. [30,35] Minimizing this time frame while still retaining optimal performance metrics is necessary for UV sintering to be considered a feasible technique for large-scale electrode fabrication. Therefore, microgrid design, trace morphology, surface chemistry, and UV light exposure will therefore all play a critical role in conductive performance and subsequently transparent heater thermal performance efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Ink formulations containing metal carboxylate salts, specifically silver neodecanoate (AgND), demonstrate a mechanically robust and highly conductive medium for fabricating silver features at low processing temperatures. [28][29][30] However, maximizing the electro-optical properties is key for TCE design to ensure that the payoff for high electrical performance does not negatively impact the resulting transparency of the electrode. Optimizing the electro-optical properties through careful selection of the TCE design, material selection and material processing conditions ensures that high conductive performance of the grids can be achieved with high optical transparency.…”
mentioning
confidence: 99%
“…Only the peaks of the (111), ( 200), ( 220), (311), and (222) planes of Ag were observed, and there were no other obvious peaks in the XRD pattern. Thus, it can be concluded that the inks had completely decomposed into Ag at 160 °C [27,28].…”
Section: Characterization Of the Ag Film After Sinteringmentioning
confidence: 95%
“…Conductive wires that are decorated in the mold with finished products can be hot-pressed by local heating, and the resistance measured after each process is almost the same. In 2021, Xiang yang Liu et al [ 17 ] developed a new method of screen-printable oxalate ink treatment based on broadband ultraviolet light, which produces traces with excellent electrical properties and is produced in a shorter time compared to thermal sintering. Together, ultraviolet light treatment and silver oxalate molecular inks provide a platform for the rapid production of conductive silver traces on cryogenic substrates and the development of new thermoforming 3D human–machine interface devices, an area of interest to both academia and industry.…”
Section: Literature Reviewsmentioning
confidence: 99%